Disiplin Anak di dalam Keluarga: Kontinuitas dan Diskontinuitas Pemikiran John Calvin di dalam Pengajaran William Gouge - Yuki Fran Siska; Benyamin Intan (Reformed Center for Religion and Society, 2022)
Discipline for children in the family has become one of the most difficult problems and challenges for parents throughout the ages. The reality of two extremes of discipline, violence and neglect, becomes an unavoidable fact and keep continues in different contexts. In particular, since the Reformation period, efforts to overcome this problem have been continuously pursued by theologians who wanted a biblical and balanced discipline. This article seeks to find the best way to deal with this problem by re-examining the work of John Calvin and William Gouge. According to his context, Calvin has given a legacy which Gouge later developed. Through a literature study with a biblical-historical approach, this study concludes that there is continuity and discontinuity between Calvin and Gouge's teaching on child discipline. This analysis has significance for today's Christian families in evaluating and resuming efforts to bring a balanced child discipline in the family.